Character and Emotional Intelligence Impact on Juvenile Delinquency: The Mediating Role of Interpersonal Intelligence - Dede Ahmad Supriatna; Achmad Hufad; Asep Saepudin; Ade Romi Rosmia; Faridah Hanim (Journal of Nonformal Education, 2025)
This study explores the role of interpersonal intelligence in mediating the influence of character strength and emotional intelligence on juvenile delinquency. Using a quantitative survey method, data were collected from 250 vocational high school students in Cianjur City through a validated questionnaire and analyzed using the SEM-PLS approach. The results showed that character strength had a negative and significant effect on juvenile delinquency, with a coefficient value of -0.321, indicating that increasing character strength can significantly reduce juvenile delinquency. In addition, emotional intelligence also showed a negative and significant effect on juvenile delinquency. This confirms that increasing emotional intelligence also contributes to reducing juvenile delinquency. Interpersonal intelligence negatively and significantly impacts juvenile delinquency, with a coefficient value of -0.161, indicating that better interpersonal skills can reduce the tendency for delinquent behavior. Furthermore, character strength and emotional intelligence were found to have a positive and significant effect on interpersonal intelligence, with coefficient values ​​of 0.370 and 0.484, respectively. Another important finding is the significant negative indirect effect of character strength and emotional intelligence on juvenile delinquency through interpersonal intelligence. This shows that increasing character strength and emotional intelligence can reduce juvenile delinquency by improving interpersonal intelligence. This study concludes that strengthening students’ character and emotional intelligence and increasing interpersonal intelligence are essential strategies for reducing juvenile delinquency